2016
DOI: 10.1111/jir.12273
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the bone health of older adults with an intellectual disability in Ireland

Abstract: Background Many risk factors have been confirmed for poor bone health among the general population including age, gender and corticosteroid use. There is a paucity of investigation among people with intellectual disability; however, research points to differing risks namely anti‐epileptic medication use, Down syndrome and poor behaviour lifestyle. Methods Data was extracted from the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing in Ireland. In total, 753 participants took part, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…Lin et al (2014) reported that in a sample of individuals with learning disability over the age of 40 more than half had either osteoporosis or osteopenia. This is supported by evidence that rates of hip fractures are three times higher in people with learning disabilities compared to the general population (Burke et al, 2016). Cheema et al's (2016) study reported that 28% of children with learning disabilities had bone mineral density profiles below the norm.…”
Section: Bone Health In People With a Learning Disabilitysupporting
confidence: 62%
See 1 more Smart Citation
“…Lin et al (2014) reported that in a sample of individuals with learning disability over the age of 40 more than half had either osteoporosis or osteopenia. This is supported by evidence that rates of hip fractures are three times higher in people with learning disabilities compared to the general population (Burke et al, 2016). Cheema et al's (2016) study reported that 28% of children with learning disabilities had bone mineral density profiles below the norm.…”
Section: Bone Health In People With a Learning Disabilitysupporting
confidence: 62%
“…People with a learning disability have increased susceptibility of developing osteoporosis due to comorbid health complications such as hypothyroidism, sideeffects from an increased use of polypharmacy including anti-epileptic and antipsychotic medications, sedentary lifestyles and lack of weight-bearing exercise, poor diet, difficulties in accessing and complying with screening for BMD, bone health typically being omitted from annual health checks and a lack of screening for vitamin and mineral deficiencies (Emerson and Baines, 2010;Frighi et al, 2014;Burke et al, 2016).…”
Section: Bone Health In People With a Learning Disabilitymentioning
confidence: 99%
“…Each of the Wave 2 participants was invited to take part and to facilitate and support the individual's participation, adaptable and accessible materials, and methods were developed. This component has been described in detail elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…People with learning disability will experience more health problems than the general population (Burke et al, ; Kerr, ), with an increased rate of falls and injuries (Finlayson et al, ). The prevalence of vitamin D deficiency has been established within the general population; yet, as far as the authors are aware there is little evidence specific to the learning disability population.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the included studies in this review examined the effect of AED on vitamin D levels finding no differences in those with and without AED prescription (McKinnon et al, , Vanlint & Nugent, and Wong et al, ). However, Burke, McCallion, Carroll, Walsh, and McCarron () showed that AEDs were strong predictors of osteoporosis in an older learning disability population and associated with a significant risk of fracture (Burke et al, ).…”
Section: Discussionmentioning
confidence: 99%